Edukasi dan Workshop 5S di Lingkungan Masyarakat dan Kehidupan Sehari Hari - Tri Widodo; Ismail Fardiansyah; Irman Maulana (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
A clean, neatly arranged and beautiful environment is something that people really desire. Because it will brings various positive impacts including: increasing the sense of comfort for the community, avoiding potential diseases and contributing to a green environment which brings many benefits. The 5S program is a program that is commonly implemented by many companies. 5S is an extension of (seiri, seiton, seiso, seiketsu, shitsuke) or usually translated as 5R (concise, neat, clean, diligent care). 5S is very suitable to be implemented in society where it is hoped that it will have an impact on creating a green environment. 5S education and workshops are carried out by providing directions along with examples. This application consists of sorting community equipment that is needed and not needed. Seiton explained that all community equipment has its proper place. Seiso by carrying out environmental cleaning is equipped with seiketsu which is routine scheduling, as well as shitsuke whose application is routine checking of the environment together to produce further improvements to the environment